ACL Prehabilitation Improves Postoperative Strength and Motion and Return to Sport in Athletes - Jamie Cunha, D.P.T; Daniel J. Solomon, M.D (Elsevier, 2022)
Prehabilitation prior to anterior cruciate ligament reconstruction should include quadriceps strengthening-improving range of motion and balance and proprioception as a minimum. Although the content and duration of prehabilitation varies in the literature, when faced with a delay between diagnosis and surgery, 4-6 weeks of prehabilitation can improve early to mid-term strength and motion and can improve the timing and odds of a patient returning to sport.